The image of reformative populism (narodnichestvo) in Russian Historiography from the 20s years of the 20th to the beginning of the 21th Century - V V Zverev (RUDN Journal of Russian History, 2009)
The article represents the analyses of the term «reformative populism (reformative narodnichestvo)» and its moderate wing from the 20s years of the 20th to the beginning of the 21th. The special attention is paid to the Lenin's conception of evolution of the public opinion in Russia of the second half of the 19st, which became the faithful methodological approach in soviet history. At the same time the author gives his own opinion to the study of this problem for the future.